Perundungan dan Stres pada Mahasiswa Kedokteran - Dewantara, Lilac; Kairupan, Bernabas H. R.; Munayang, Herdy (e-CliniC, 2025)
Abstract: Bullying tend to occur in the educational process, including inside medical institutions. Bullying is associated with high level of stress, which may influence various aspects of life, including quality of service and patient safety. This study aimed to report various literature regarding bullying and stress in medical students. This was a systematic review study using three databases, namely Google Scholar, PubMed, and Clinical Key. The literatures used should be in Indonesian or English, published during the last five years. Based on the 10 studies reviewed, it was found that bullying still occurred in medical education, with a prevalence of 16% up to 86.8%. The major target of bullying was females. Bullying influenced one’s psychological, academic, and social aspects. Psychologically, bullying was associated with high level of stress, anxiety, and depression. In conclusion, bullying among medical students is associated with stress. Keywords: bullying; stress; medical students   Abstrak: Perundungan seringkali terjadi dalam proses pendidikan, termasuk di dalam institusi kedokteran. Perundungan dikaitkan dengan stres yang tinggi, yang dapat memengaruhi berbagai aspek kehidupan, termasuk mutu pelayanan dan keselamatan pasien. Penelitian ini bertujuan untuk melaporkan kajian pustaka dari perundungan dan stres pada mahasiswa kedokteran. Penelitian ini menggunakan metode systematic literature review dengan menggunakan tiga database, yaitu Google Scholar, PubMed, dan Clinical Key. Literatur yang digunakan dalam bahasa Indonesia atau bahasa Inggris, yang diterbitkan dalam lima tahun terakhir. Berdasarkan hasil reviu dari 10 penelitian yang didapat, ditemukan bahwa perundungan masih sering terjadi dalam pendidikan kedokteran dengan prevalensi 16% hingga 86,8%. Mayoritas sasaran perundungan ialah perempuan. Perundungan memengaruhi aspek psikolgis, akademis, dan sosial. Secara psikologis, perundungan diasosiasikan dengan stres yang tinggi, kecemasan, dan depresi. Simpulan penelitian ini ialah perundungan pada mahasiswa kedokteran diasosiasikan dengan stres. Kata kunci: perundungan; stres; mahasiswa kedokteran